2014
DOI: 10.1002/2013jf002965
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sediment properties on deltaic processes and morphologies: A numerical modeling study

Abstract: There is a pressing need to understand how different delta morphologies arise because morphology determines a delta's ecologic structure, resilience to relative sea-level rise, and stratigraphic architecture. We use numerical modeling (Delft3D) to explain how deltaic processes and morphology are controlled by the incoming sediment properties. We conducted 36 experiments of river-dominated delta formation varying the following sediment properties of the incoming grain-size distribution: the median, standard dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
188
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(198 citation statements)
references
References 67 publications
10
188
0
Order By: Relevance
“…Long-term morphologic calculations are rare due to computer limitations and lack of spatially and temporally dense data of mud in the bed. For deltas, on the other hand, long-term morphologic development by numerical modelling (Edmonds and Slingerland, 2009;Caldwell and Edmonds, 2014;Burpee et al, 2015) showed large effects of mud on plan shapes, patterns and dynamics with fairly simplistic sediment transport processes. In particular, cohesion reduces the ability to re-erode, resulting in more stable bars and levees and longer and deeper channels.…”
Section: Past and Novel Modelling Approaches For Sand-mud Mixturesmentioning
confidence: 99%
“…Long-term morphologic calculations are rare due to computer limitations and lack of spatially and temporally dense data of mud in the bed. For deltas, on the other hand, long-term morphologic development by numerical modelling (Edmonds and Slingerland, 2009;Caldwell and Edmonds, 2014;Burpee et al, 2015) showed large effects of mud on plan shapes, patterns and dynamics with fairly simplistic sediment transport processes. In particular, cohesion reduces the ability to re-erode, resulting in more stable bars and levees and longer and deeper channels.…”
Section: Past and Novel Modelling Approaches For Sand-mud Mixturesmentioning
confidence: 99%
“…In the absence of waves and tides, channel leveeing and bifurcation lead to the development of crenulated shorelines typical of fluvial dominance, with plan-view morphologies determined by sediment size [Orton and Reading, 1993;Caldwell and Edmonds, 2014] and cohesion [Edmonds and Slingerland, 2009]. Wind waves discourage accumulation of finegrained sediment at the delta mouth, and tend to sculpt delta shorelines into a cuspate shape consisting of sandy shorelines composed of shoreline-parallel beach ridges .…”
Section: Introductionmentioning
confidence: 99%
“…Although dimensions vary, this general morphology has been observed on the Wax Lake Delta (Shaw et al, 2016b;Shaw and Mohrig, 2014), Brant's Pass crevasse on the birds-foot delta of the Mississippi River (Esposito et al, 2013), the Mobile and Apalachicola river deltas (Edmonds et al, 2011b) and the St. Clair River Delta (Figure 1b; NOAA, 2017). Additionally, numerical models often produce this morphology (Caldwell and Edmonds, 2014;Geleynse et al, 2010;5 Liang et al, 2016). These deltas can be qualitatively classified as river-dominated (Galloway, 1975), both by their large fluvial sources and relatively small winds and tides.…”
Section: Bathymetry and Flow Patterns On River-dominated Deltasmentioning
confidence: 99%
“…In order to achieve some validation independent of the Wax Lake Delta, the FD2C model was also evaluated on four numerical river deltas originally presented by Caldwell and Edmonds (2014). These deltas were modelled using Delft3D on a 25 x 25 m 2 grid.…”
Section: Estimating Channel Tip Location 10mentioning
confidence: 99%
See 1 more Smart Citation